Growth Response Of Tomato (Solanum lycopersicum) To The Combination Of Aloe Vera And Tauge (Flammulina velutipes) Extract) - Yuli Erpiana Harahap; Indayana Febriani Tanjung; Adella Shaharani; Wanda Wanda Syahfitri (Universitas Pekalongan, 2023)
Utilization of appropriate plant species, one of which is aloe vera (Aloe vera) and bean sprouts (Flammulina velutipes), which are plant species whose extracts can be utilized as ZPT (Growth Regulatory Substances). The research was conducted in November 2022 with a total of 3 weeks of observations. The purpose of this study was to determine the growth response of tomato (Solanum lycopersicum) to a combination of aloe vera and bean sprouts (Flammulina velutipes) extracts. The materials used included tomato seeds, water, aloe vera extract and bean sprouts while the tools used included polybags, soil testers, hoes, gembor and stationery. The method in this study was carried out by RAK (Random Random Control) using 4 treatments including 0 cc, 15 cc, 20 cc, 25 cc with 3 weeks of observation. Watering is done 3 days once a week. The results obtained showed that treatment 3 (20 cc) had a significant impact on tomato growth.